ARE THEIR YOUNG CORONARIES OLD ENOUGH? ANGIOGRAPHIC FINDINGS IN YOUNG PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Anjum, Muhammad; Zaman, Muhammad; Ullah, Fareed (Journal of Ayub Medical College Abbottabad, 2019)
Background: Increasing affection of younger patients with ischemic heart disease is an enhanced concern in developing Asian nations. This study elaborates the morphology and distribution of coronary lesions in young Asians presenting with acute coronary syndrome (ACS). Methods: Patients (aged ‰¤35 years) with (ACS) undergoing angiography were studied. Their angiographic disease was analysed to determine the common sites, severity and types (AHA and SCAI) of lesions. The association of LV dysfunction with lesion parameters was identified. Patients with cocaine or other drug abuse and valvular heart disease were excluded. Results: Two hundred and twenty-one patients aged 16-35 (31.4±3.5) years were studied with predominant males (195, i.e., 88.2%). On angiography 51 (23.1%) patients showed normal coronaries while 108(48.9%) had single, 48 (21.7%) had double and 14 (6.3%) had multivessel disease. On the whole, involvement of left anterior descending artery (LAD) either singly or in combination with other vessels was seen in 146 (66%), right coronary artery (RCA) in 56 (25.3%), left circumflex (LCX) in 43 (19.5%) and left main stem in 06 (2.7%) of total patients. Regarding lesion characteristics, tight lesions (45.4%), AHA type-A (47.8%) and SCAI-I (70.1%) lesions were common. The mid segment was commonly involved in LAD and LCX while proximal segment in RCA. Severe LV dysfunction was associated with presence of LAD disease. Conclusions: Coronary angiograms can be normal in up to one fourth of young ACS patients. Others show a predominance of LAD artery involvement with morphologically simple lesions. Keywords: coronary angiography; coronary lesions; Young patients